Exploring Communication Breakdowns in Marriages Affected by Emotional Neglect - Yousefi, Zahra (Journal of Psychosociological Research in Family and Culture, 2026)
Objective: This study aimed to explore the lived experiences of communication breakdowns in marital relationships affected by emotional neglect.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 21 adult participants (12 women and 9 men) residing in Iranian. Participants were purposively selected based on self-reported experiences of emotional neglect in current or past marriages of at least five years. Data collection continued until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo 14 software. Thematic analysis followed Braun and Clarke’s six-step framework to identify recurring patterns related to emotional neglect and communication dynamics.Findings: Four major themes emerged from the data: emotional unavailability, ineffective communication patterns, psychosocial impact of neglect, and barriers to reconnection. Participants consistently reported emotional detachment, disengaged listening, and suppression of emotional expression as core aspects of emotional neglect. Communication breakdowns included verbal withdrawal, misinterpretation of intent, and conflict escalation. Emotional neglect was linked to psychological consequences such as self-blame, isolation, diminished self-esteem, and hopelessness about the relationship. Fear of vulnerability, lack of emotional skills, and cultural norms emerged as key barriers to emotional repair. The results highlight emotional neglect as a relational process that undermines emotional safety and communicative trust.Conclusion: Emotional neglect in marriage is a pervasive and underrecognized dynamic that contributes significantly to communication breakdowns and psychological distress. This study underscores the importance of identifying emotional neglect in therapeutic settings and developing interventions that focus on emotional literacy, attunement, and trust-building.